O36-1 Higher noise levels are associated with increased injury rates in us coal miners. (1st September 2016) - Volk, Lindsay; Harris, Gerald; Cohen, Robert; Almberg, Kirsten; Graber, Judith M
Abstract : Background: Mining has long been recognised as a dangerous occupation, with exposure to hazardous sound levels leading to permanent hearing loss a pervasive risk. Increased noise exposure has been associated with increased injury risk in other industries, but this relationship has not been explored among US miners. We examined this relationship among US coal miners. Methods: US Mine Safety and Health Administration (MSHA) regulatory datasets from 2000 to 2013 were linked using a unique mine identifier and year of observation (mine-year); datasets included: noise-surveys (30-CRF-part 62), citations, mine employment, and, injury reports (30-CRF-part 50). The association between sound levels (as an 8-hour time-weighted average) and injury rates were examined using bivariate analysis and Poisson regression. Covariates included mine characteristics (e.g., number of employees, coal type, existence of a safety committee) and noise survey/citation results (e.g., hearing protection worn by the miner surveyed, violation issuance). Results: Among the 18, 589 unique mine-years were 59, 301 injury records, 4, 129 mines, and 149, 045 noise measurements. In regression analysis, factors significantly and positively associated with injury rates included: noise level (1.8% [95% CI: 1.7, 1.8] increase for each decibel increase in sound level); working in an anthracite vs. bituminous mine (20%, 95% CI: 12.7, 27.3); and, the existence of a safety committee (5.9%, 95% CI: 3.7, 7.9). Protective factors included use of any hearing protection (e.g. cap only −6.1%, 95% CI: −3.9, −8.2) and whether the survey resulted in a violation (−14.7%, 95% CI: −6.4, −23.0). Discussion: We observed a positive and significant relationship between increased noise and increased injury rates in US coal mines. This may be the result of more machinery operating and at higher rates of production, resulting in more injuries as well as interference with communication. Further work is needed to understand the mechanism of this relationship and the contribution of other factors.